Significant triboelectric enhancement using interfacial piezoelectric ZnO nanosheet layer. (October 2017) - Narasimulu, Anand A.; Zhao, Pengfei; Soin, Navneet; Prashanthi, Kovur; Ding, Peng; Chen, Jinkai; Dong, Shurong; Chen, Li; Zhou, Erping; Montemagno, Carlo D.; Luo, Jikui
Abstract: Utilising an interfacial piezoelectric ZnO nanosheet layer, a significant enhancement in the power density is reported for the triboelectric nanogenerators (TENG) based on phase inversion membranes of polyvinylidene fluoride (PVDF) and polyamide-6 (PA6). At an applied force of 80 N, the TENG device incorporating electrochemically deposited ZnO nanosheets produces an output voltage of 625 V and a current density of 40 mA m −2 (corresponding a charge density of 100.6 μC m −2 ), respectively; significantly higher than 310 V and 10 mA m −2 (corresponding a charge density of 77.45 μC m −2 ) for the pristine TENG device. The enhancement in the surface charge density provided by the interfacial piezoelectric ZnO layer is also reflected in the high piezoelectric coefficient d33 (−74 pm V −1 ) as compared to the pristine fluoropolymer membranes (−50 pm V −1 ). For tribo-negative membranes incorporating the interfacial ZnO layer, piezoelectric force microscopy measurements further show enhanced domain size which can be attributed to the interfacial dipole-dipole interaction with the ferroelectric polarisation of PVDF, which promotes the alignment with the polar axis of ZnO. Under compressive stress, the piezoelectric potential thus produced in the ZnO nanosheets provides charge injection on to the surface of ZnSnO3 -PVDF membrane, improving the charge density, which in-turn significantly enhances the power density from 0.11 to 1.8 W/m 2 . The TENG devices thus fabricated using a facile electrochemical deposition and phase inversion technique show enhanced output power without the need for high electric field poling or external charge injection process by relying on the coupling of triboelectric and piezoelectric effects. Graphical abstract: Highlights: The TENG output enhancement mechanism is based on the coupling of triboelectric and piezoelectric effects. The electrochemical deposited piezoelectric ZnO piezoelectric nanosheets as the interfacial layer. The well-aligned ZnO nanosheets assist the formation of PVDF with high β-phase and crystallinity. The ZnO nanosheet layer inject high charge density into the PVDF layer through polarisation under pressure.